2023
DOI: 10.1093/jjco/hyad170
|View full text |Cite
|
Sign up to set email alerts
|

Enfortumab vedotin following platinum-based chemotherapy and immune checkpoint inhibitors for advanced urothelial carcinoma: response, survival and safety analysis from a multicentre real-world Japanese cohort

Makito Miyake,
Nobutaka Nishimura,
Yuki Oda
et al.

Abstract: Objective Real-world evidence regarding enfortumab vedotin for unresectable or metastatic urothelial carcinoma is scarce, particularly in Japan. We investigated real-world data focusing on patient background, previous treatments, response, survival and adverse events in patients receiving enfortumab vedotin. Methods A multicentre database was used to register 556 patients diagnosed with metastatic urothelial carcinoma from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Notably, the response rate for pure UC reached 58%, contrasting with 42% in patients with subtype histology [9]. In these two Japanese reports, subtype information is not available [10,11]. In our study, the response rate among patients with histological subtypes was 25% (2/8), with a response rate of 75% in those with pure UC, mirroring the UNITE study [9].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Notably, the response rate for pure UC reached 58%, contrasting with 42% in patients with subtype histology [9]. In these two Japanese reports, subtype information is not available [10,11]. In our study, the response rate among patients with histological subtypes was 25% (2/8), with a response rate of 75% in those with pure UC, mirroring the UNITE study [9].…”
Section: Discussionsupporting
confidence: 69%
“…In two other multicenter retrospective studies from Japan, Taguchi et al reported that the ORR was 46%, and the median PFS and OS from the start of EV were 5 and 11 months, respectively, in 39 patients from nine institutions. Additionally, Miyake et al reported that the ORR was 56% (CR, 0%; PR, 0%), and the median PFS and OS from the start of EV were 9 and 16 months, respectively, in 34 patients from 19 institutions [10,11]. These retrospective studies concluded that the efficacy of EV therapy in real-world settings was comparable to that reported in clinical trials.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the biomarker analysis of EV treatment was very limited [24][25][26]. In the past, potential prognostic variables were identified that included a variety of inflammation and nutritional markers such as CRP, NLR, and the platelet-lymphocyte ratio [16][17][18][19]. In particular, concerning the value of the prognostic biomarker of CRP in the analysis, Klumper et al highlighted that the CRP response predicts immunotherapy response and outcomes in mUC independently in the 154 patients with mUC in the multi-center observational study by [16].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when the GNRI is high, this may predict a good prognosis in those patients with la/mUC treated with ICIs. Moreover, several studies showed that the serum C-Reactive Protein (CRP), a marker of inflammation, was a prognostic marker in the systemic therapy including EV for la/mUC [13][14][15][16][17][18][19]. However, there was no evidence as to whether the GNRI or CRP was a better prognostic marker of EV therapy.…”
Section: Introductionmentioning
confidence: 99%